Cell Division and Deoxyribonucleic Acid Synthesis after a Nutritional Shift-Up of Saccharomyces cerevisiae - Jacobson, G. K. (1973)
Rates of cell division and deoxyribonucleic acid synthesis after shift-up with grande and mitchondrial deoxyribonucleic-acid-less petite yeasts were studied. The results indicate that simple eukaryotes behave as prokaryotes.